Parental experiences on the role of wheelchairs in the lives of children with mobility impairments : a qualitative exploration in Dubai - Liebenberg, Anjanet Wanda (Stellenbosch : Stellenbosch University, 2019)
Thesis (MHumanRehabSt)--Stellenbosch University, 2018.